Urban Air Quality in Europe - Viana, Mar.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book provides an overview of air quality in urban environments in Europe, focusing on air pollutant emission sources and formation mechanisms, measurement and modeling strategies, and future perspectives. The emission sources described are biomass burning, vehicular traffic, industry and agriculture, but also African dust and long-range transport of pollutants across the European regions. The impact of these emission sources and processes on atmospheric particulate matter, ozone, nitrogen oxides and volatile and semi-volatile organic compounds is discussed and critical areas for particulate matter and nitrogen dioxide in Europe are identified. Finally, this volume presents future perspectives, mainly regarding upcoming air quality monitoring strategies, metrics of interest, such as submicron and nanoparticles, and indoor and outdoor exposure scenarios.
Critical Areas for Compliance with PM10 and NO2 Limit Values in Europe -- The Evolution and Control of NOx Emissions from Road Transport in Europe -- Air Pollution by Ozone Across Europe -- Persistent Organic Pollutants in the European Atmosphere -- Wildfires as a Source of Aerosol Particles Transported to the Northern European Regions -- Residential Wood Burning: a Major Source of Fine Particulate Matter in Alpine Valleys in Central Europe -- Ammonia Emissions in Europe -- Road Traffic: a Major Source of Particulate Matter in Europe -- Source Apportionment of Airborne Dust in Germany: Methods and Results -- Air Quality in Urban Environments in the Eastern Mediterranean -- Anthropogenic and Natural Constituents in PM10 at Urban and Rural Sites in North-Western Europe: Concentrations, Chemical Composition and Sources -- Particulate Matter and Exposure Modelling in Europe -- Air Pollution Monitoring Strategies and Technologies for Urban Areas -- Number Size Distributions of Submicron Particles in Europe -- Indoor-Outdoor Relationships of Particle Number and Mass in European Cities -- Nanoparticles in European Cities and Associated Health Impacts.
Keywords: Environmental sciences; Analytical biochemistry; Geochemistry; Environmental chemistry; Environmental protection; Environment; Atmospheric Protection/Air Quality Control/Air Pollution; Geochemistry; Analytical Chemistry; Environmental Chemistry